2021
DOI: 10.3390/ijerph18063244
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Computer-Assisted Dynamic Navigation as a Function of Different Intraoral Reference Systems: An In Vitro Study

Abstract: The aim of this in vitro study was to determine whether the process chain influences the accuracy of a computer-assisted dynamic navigation procedure. Four different data integration workflows using cone-beam computed tomography (CBCT), conventional impressions, and intraoral digitization with and without reference markers were analyzed. Digital implant planning was conducted using data from the CBCT scans and 3D data of the oral models. The restoration of the free end of the lower jaw was simulated. Fifteen m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…The results of this investigation confirmed the suitability of the Denacam dCAIS system regarding accuracy in oral implant surgery as previous investigations already demonstrated (Edelmann et al, 2021; Schnutenhaus et al, 2021; Spille et al, 2021). The present study was conducted to investigate the accuracy in three different regions with two different dCAIS workflows and to compare it with the gold standard method of sCAIS (Gargallo‐Albiol et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this investigation confirmed the suitability of the Denacam dCAIS system regarding accuracy in oral implant surgery as previous investigations already demonstrated (Edelmann et al, 2021; Schnutenhaus et al, 2021; Spille et al, 2021). The present study was conducted to investigate the accuracy in three different regions with two different dCAIS workflows and to compare it with the gold standard method of sCAIS (Gargallo‐Albiol et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…The camera observes the position of the handpiece in relation to the marker and shows on a screen the positional and axial corrections which have to be performed in order to realize the virtually planned implant position. First in‐vitro investigations and one clinical study showed promising results regarding the accuracy (Duré et al, 2021; Edelmann et al, 2021; Schnutenhaus et al, 2021; Spille et al, 2021). One interesting issue of this novel technique for guided surgery is represented by the different workflows that can be used to include the reference elements into the software for planning: The reference element can either be placed and fixed during CBCT acquisition with thermoplastic material, or this matrix can virtually be placed into a pre‐existing CBCT, then 3D‐printed and fixed on the patient's teeth during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…First, the CBCT scan errors were determined by voxel size, exposure time, field of view, and metal artifacts, which influenced the initial data acquisition [ 31 ]. Similar to the dynamic dental implant navigation system, the placement and fixation of the marker were affected by the marker type, fabrication, and position using the robotic surgery system [ 32 ]. In addition, the robot arm has intrinsic errors, and the average positioning accuracy (trueness) is 0.156 mm, provided by the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…The mouth opening, possible movements of the patient and the possibly restricted view of the surgical field in the posterior region can have an influence on the accuracy [27]. The material of the reference markers used can lead to artifacts and thus have an influence on the accuracy [28] as well as the positioning of the fiducial markers themselves [29]. Another possible source of inaccuracies are the individual steps of the digital workflow, which can add up [11].…”
Section: Introductionmentioning
confidence: 99%